2015
DOI: 10.15376/biores.10.2.2167-2176
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Activity In Vivo and In Vitro of Two Feruloyl Oligosaccharides Preparations Produced from Wheat Bran and Fermented by Aureobasidium pullulans

Abstract: The antioxidant functions of two feruloyl oligosaccharide (FO1 and FO2) were investigated in vivo and in vitro. Effects of FO1 and FO2 on hemolysis of rat red blood cell (RBC) and malondialdehyde (MDA) formation in rat liver homogenate and rat liver mitochondria in vitro were studied. Hemolysis of rat RBC and MDA formation in rat liver homogenate and rat liver mitochondria were inhibited in a dosagedependent manner by FO1 and FO2 in the tested concentration range of 0.5 to 10 mg/mL. The results showed that FO1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 14 publications
1
2
0
Order By: Relevance
“…In the present study, free ferulic acid was released, and antioxidant capacity in vitro was elevated in PCFWH. Previous studies also indicated that FOs were produced in Aureobasidium pullulans fermented WB, and this fermented material improved serum MDA content of S180 tumor-bearing mice [8]. In the present study, the 10% PCFWH treatment elevated serum SOD, CAT activities, indicating that the oxidative status of hens was improved.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…In the present study, free ferulic acid was released, and antioxidant capacity in vitro was elevated in PCFWH. Previous studies also indicated that FOs were produced in Aureobasidium pullulans fermented WB, and this fermented material improved serum MDA content of S180 tumor-bearing mice [8]. In the present study, the 10% PCFWH treatment elevated serum SOD, CAT activities, indicating that the oxidative status of hens was improved.…”
Section: Discussionsupporting
confidence: 74%
“…The FOs also display great antioxidant activity in vitro and in vivo [ 7 ]. Recently, production of FOs through fermentation by Aureobasidium pullulans 2012 was studied and the yield of FOs could reach 774 nmol/L [ 8 ], and these FOs exert an antioxidant effect [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…XOs inhibited the hemolysis of rat red blood cell and malondialdehyde formation in rat liver homogenate and rat live mitochonldria in vitro [57]. The XOs had antioxidative activity and increased the activity of SOD and GSH-Px in serum of tumor-bearing mice [58,59]. The XOs produced by Bacillus aerophilus xylanase from corncob xylan showed antioxidant capacity with IC 50 of 1 mg ml −1 [60].…”
Section: Wheat Bran Insoluble Xylanmentioning
confidence: 99%